Increasing the Donor Pool: Consideration of Prehospital Cardiac Arrest in Controlled Donation After Circulatory Death for Liver Transplantation. Issue 1 (20th December 2013) - Elaffandi, Ahmed H.; Bonney, Glenn K.; Gunson, Bridget; Scalera, Irene; Mergental, Hynek; Isaac, John R.; Bramhall, Simon R.; Mirza, Darius F.; P.R. Perera, M. Thamara; Muiesan, Paolo
Abstract : Donor warm ischemia has implications for outcomes after liver transplantation (LT) using organs from donation after circulatory death (DCD) donors. Prehospital cardiac arrest (PHCA) before donation may generate a further ischemic insult. The aim of this single‐center study of 108 consecutive DCD LT procedures was to compare the outcomes of PHCA and non‐PHCA cohorts. A review of a prospectively collected database of all DCD grafts transplanted between January 2007 and October 2011 was undertaken to identify donors who had sustained PHCA. The unit policy was to consider such donors when transaminase levels were ≤4 times the normal range and had an improving trend. Twenty‐six of the 108 DCD transplants were from DCD donors with PHCA, and 82 were in the non‐PHCA cohort. A comparative analysis of the PHCA and non‐PHCA cohorts showed better short‐term results (a low incidence of acute kidney injury) for the PHCA group but satisfactory long‐term results for both groups with no significant differences in graft or patient survival between them. In conclusion, a careful donor selection policy for including PHCA DCD donors with normalized liver function tests or transaminase levels ≤ 4 times the norm resulted in successful transplantation and could boost the donor pool with no adverse outcomes. Liver Transpl 20:63‐71, 2014 . © 2013 AASLD.